2012
DOI: 10.5455/vetworld.2012.754-761
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bupivacaine, xylazine and buprenorphine with ketamine combination for spinal analgesia in buffalo calves

Abstract: Aim : The study was undertaken to compare the clinical efficacy of lumbosacral spinal analgesia produced using bupivacaine, xylazine and buprenorphine with ketamine combination in buffalo calves Materials and Methods: 36 male buffalo calves of seven to eight months of age and weighing 60 to 75 kg were used to evaluate the efficacy and safety of lumbosacral spinal analgesia produced by bupivacaine 0.25mg/kg, xylazine 0.05 mg/kg and buprenorphine 20 µg/kg in combination with ketamine 2.5mg/ kg and divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…According to our knowledge dorsolumber epidural analgesia not previously used in buffalos, although, it is widely used for flank laparotomy in cattle (Lee, et al, 2004, 2005, and 2006, Hiraoka, et al, 2007. However, epidural administration of xylazine with other local anesthetics was evaluated in buffaloes calves (Pathak, et al, 2012). Insertion of the epidural needle into the epidural space between the last thoracic and first lumber vertebrae was successful in 8 of 10 buffalos (80 %) from the first trial, while the rest 20 % was successful from the second trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our knowledge dorsolumber epidural analgesia not previously used in buffalos, although, it is widely used for flank laparotomy in cattle (Lee, et al, 2004, 2005, and 2006, Hiraoka, et al, 2007. However, epidural administration of xylazine with other local anesthetics was evaluated in buffaloes calves (Pathak, et al, 2012). Insertion of the epidural needle into the epidural space between the last thoracic and first lumber vertebrae was successful in 8 of 10 buffalos (80 %) from the first trial, while the rest 20 % was successful from the second trial.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, epidural administration of xylazine hydrochloride produces less pronounced cardiopulmonary effect compared to intramuscular and intravenous injection (Rehage et al, 1994;Junhold and Schneider, 2002). After epidural administration of xylazine in animals, the injected animals showed signs of sedation, which, attributed to the systemic effect of xylazine after its absorption to the systemic circulation through the epidural vein and lymphatic (Danghee and Chunsik, 2001;Pathak et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, these values gradually returned to base value. Pathak et al (2012) [12] recorded reduction in Hb and PCV values but the changes were non-significant after intraspinally administration of buprenorphine at lumbosacral space in buffalo calves. Fall in Hb, PCV and TLC after propofol has also been reported by Kelawala et al (1991) [8] in goats and Singh et al (2014) [15] in buffalo calve.…”
Section: Hematological Profilesmentioning
confidence: 98%
“…[2] with propofolbuprenorphine in atropinized dogs. Similarly, Kumar et al (2010) [9] also reported hyperglycemia after administration of propofol premeditated with cannabis indica (Bhang) extract in dogs whereas, Pathak et al (2012) [12] reported nonsignificant variation in plasma glucose concentration after intraspinal administration of buprenorphine in buffalo calves. In the present study, the increased serum glucose level might be attributed to decreased membrane transport of glucose, decreased glucose utilization, impaired insulin activity or increased concentration of adrenocortical hormones.…”
Section: Hematological Profilesmentioning
confidence: 98%
“…This observation corresponds with the previous findings (Trim, 1989;and Runa et al 2008). Pathak et al (2012) recorded the longest duration of complete analgesia with combination of bupivacaine and ketamine in buffalo calves. The protein binding characteristics of local analgesic agents influence the duration of action (Gissen et al, 1980).…”
Section: Discussionmentioning
confidence: 99%